Solution:
1. Notice that x^2 - 25 and 25 - x^2 are negatives of each other:
- 25 - x^2 = -(x^2 - 25)
2. Rewrite the expression:
- \frac{3}{x^2-25} - \frac{9}{25-x^2} = \frac{3}{x^2-25} - \frac{9}{-(x^2-25)}
3. Simplify the second term:
- \frac{9}{-(x^2-25)} = -\frac{9}{x^2 - 25}
4. Rewrite the expression with a common denominator:
- Original expression: \frac{3}{x^2-25} - \frac{9}{25-x^2}
- Same terms: \frac{3}{x^2-25} + \frac{9}{x^2 - 25}
5. Combine the fractions:
- \frac{3 + 9}{x^2 - 25} = \frac{12}{x^2 - 25}
6. Factor the denominator x^2 - 25 as a difference of squares:
- x^2 - 25 = (x - 5)(x + 5)
7. Simplified expression:
- \frac{12}{(x - 5)(x + 5)}